Semen Analysis of Covid-19 Survivors and Uninfected Men: Examining the Motility, Concentration, Vitality, and Morphology Parameters of Spermatozoa - Sri Musta'ina; Eko Budi Siswidiyanto; Pety Narulita; Agustinus; Aucky Hinting; Atika; Zakiyatul Faizah (Folia Medica Indonesiana)
Highlights: 1. Spermatozoa can be affected by coronavirus disease 2019 (COVID-19) due to a disruption in spermatogenesis, leading to a decline in semen quality. 2. This study compared the semen quality of COVID-19 survivors and those who had not been infected with COVID-19, specifically on the first spermatogenesis cycle following the confirmation of COVID-19 infection. 3. This study is distinctive since no previous research in Indonesia has examined the semen quality parameters, such as the concentration, morphology, motility, and vitality of spermatozoa, in men who had a COVID-19 infection.